2020
DOI: 10.1111/head.13940
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Headache Characteristics in COVID‐19: Headache Can Be an Isolated Symptom

Abstract: Headache was reported in up to one‐third of the hospitalized patients; yet, the clinical characteristics of headache associated with coronavirus disease 2019 (COVID‐19) have not been defined. This observational case study included patients who were consulted to headache unit due to headache and had COVID‐19 illness. Headache features in 13 PCR‐confirmed COVID‐19 patients with mild symptoms were reported. Headache was the isolated symptom of the COVID‐19 in 3 patients and emerged as an early symptom during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 17 publications
5
71
1
4
Order By: Relevance
“…Therefore, epidemic prevention experts recommend paying attention to good personal hygiene and food handling practices. In addition, neurological symptoms such as headache, loss of sense of smell, amblyopia, weakness, and myalgia were described in some COVID-19 patients [ 5 , 74 , 75 ]. Our results show that the expression ratio of ACE2 in the cortex and substantia nigra of healthy people is higher than that in AT2 cells, which indicates that SARS-CoV-2 can also invade the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, epidemic prevention experts recommend paying attention to good personal hygiene and food handling practices. In addition, neurological symptoms such as headache, loss of sense of smell, amblyopia, weakness, and myalgia were described in some COVID-19 patients [ 5 , 74 , 75 ]. Our results show that the expression ratio of ACE2 in the cortex and substantia nigra of healthy people is higher than that in AT2 cells, which indicates that SARS-CoV-2 can also invade the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the mechanism of CNS involvement in patients with COVID-19 have been carried out, and the main mechanism for damage was found to be inflammationcausing blood-brain barrier deterioration and inflammation of endothelial cells in vascular and cerebral tissues (34). These can explain the main migraine-like characteristics of some description in the literature (14)(15)(16). More should however be explained, possibly through larger studies on headache characteristics together with other parameters on inflammation, thrombophilic alteration, brain histology in autopsies, brain scan, and perfusion.…”
Section: Implications For Further Researchmentioning
confidence: 99%
“…Presence of headache was linked to other central nervous system (CNS) manifestations in patients with COVID-19, suggesting that it is also a CNS-associated infectious disease (13). Headache in patients with COVID-19 does not seem to have any particular characteristics, as it is described as tension-type headache or migraine without aura (14)-the two most frequently observed types of headache (12), or a migraine-like headache type (15,16). As in previous reports on other coronaviruses, headache was an important symptom; we hypothesized the same for COVID-19 and intended to explore if it carries a prognostic value for early detection of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The Prevalence of headache was also reported to be as high as 70% in multicenter European study [ 58 ]. Additionally, headache was found to be an isolated symptom of COVID-19 in some cases [ 59 ]. A retrospective cohort study by Trigo and colleagues assessed the factors that are associated with the presence of headache in hospitalized COVID-19 patients and found that the frequency of headache was 23.7%.…”
Section: Neurological Complicationsmentioning
confidence: 99%